Saliva parameter analysis on smoker and non smoker patients exposed to intraoral radiography - Rafikah Hasyim; Aryadi Arsyad; Irene E. Rieuwpassa; Dwi P. Wulansari (Journal of Dentomaxillofacial Science, 2019)
Objective: To analyze saliva parameter such as salivary pH, total protein, buffer capacity, as well as sodium and potassium level on smoker and non smoker patients after exposed to intraoral radiography.Material and methods: This study was an observational study with cross-sectional design. Samples were smoker and non smoker patients who were referred to Dental Hospital Hasanuddin University. Saliva samples were taken by draining method. Samples were transferred immediately to Laboratory of Biochemistry, Faculty of Mathematics and Science to be processed regarding saliva pH, saliva total protein, buffer capacity, as well as saliva sodium and potassium level. Saliva pH were measured with pH meter Hanna instruments, total protein with Lowryâ€™s method, buffer capacity with Ericcsonâ€™s method, sodium and potassium level with atomic absorption spectrophotometer Parking Elmer A400. Data were then analyzed with statistical test Kolmogorov Smirnov, independent t-test, and oneway Anova with p<0.05 were considered statistically significant.Result: There were no significant difference on salivary pH, buffer capacity and potassium level between smoker group and non smoker group (p>0.05) before exposed to intraoral radiography, but we found significant difference on saliva total protein and sodium level between smoker and non smoker group (p<0.05) before radiography exposure. There were no significant change on salivary pH, total protein, buffer capacity, sodium and potassium level after exposed to intraoral radiography (p>0.05) on both smoker and non smoker group.Conclusion: Exposure of intraoral radiographs did not have significant effect on salivary pH, total protein, buffer capacity, as well as sodium and potassium level.Â